The Effect of Work Environment and Work Discipline On Performance Of Pamong Praja Police Unit (Satpol Pp) Karawang Performance - Rizki Widiyanto; Budi Rismayadi; Neni Sumarni (Trigin Publisher, 2022)
The purpose of this study was to obtain empirical evidence and to find clarity of phenomena and conclusions about the effect of the work environment and work discipline on employee performance in the civil service police unit in Karawang regency. This research was conducted with descriptive quantitative methods and verification. The data analysis technique used is path analysis technique. From the results of the research data analysis, the following conclusions were drawn: The work environment of the Karawang district civil service police unit was good, the work discipline of the Karawang district civil service police unit was good, the performance of employees in the Karawang district civil service police unit was good. There is a low correlation between the work environment and work discipline, there is no partial effect of the work environment on employee performance, there is a partial effect of work discipline on employee performance and there is a simultaneous influence between work environment and work discipline on the performance of the civil service police unit in Karawang regency